INTEGER QUADRATIC OPTIMIZATION MODEL TO SOLVE SUPPLIER SELECTION PROBLEM WITH BUDGETARY CONSTRAINT - Sagita, Hendry; Sutrisno, Sutrisno; Ratnasari, Lucia (MATEMATIKA, 2017)
In this paper, we propose an integer quadratic optimization model to determine the optimal decision for a supplier selection problem. The decision is the optimal product volume that has to be purchased from each supplier so that the total cost is minimum and the constraints are satisfied. The cost function that we used is containing the purchasing cost, transportation cost, penalty cost for product that not satisfy the quality level, penalty cost for product that is late and the holding cost whereas the constraints are consisting of supplier capacity constraint, demand satisfying, supplier assignment, inventory management, and budget constraint. A numerical experiment with generated random data is given to illustrate how the supplier selection problem can be solved by using the proposed mathematical model. From the results, the optimum product volume from each suppliers was determined so that the total cost is minimum.